Drying and mathematical modelling for the decelerated rancidity of treated jasmine brown rice using different drying media - Junka, Nittaya; Rattanamechaiskul, Chaiwat; Wongs-Aree, Chalermchai; Soponronnarit, Somchart (My University, 2021)
Jasmine brown rice (JBR) attains a rancid odour because of lipid deterioration, which reduces its shelf life. This study focused on preserving JBR's stability through drying in a fluidised bed at 100–150 °C using different drying media: hot air (HA), humidified hot air (HHA), and superheated steam (SHS). The JBR and the rancid odour caused by thiobarbituric acid (TBA) were analysed. A mathematical model was developed for the drying process, and associated equations were formulated to predict the mechanism underlying changes in TBA during 180 days of storage. The dried samples became harder owing to gelatinisation of starch and decrease in 2-acetyl-1-pyrroline volatility. Changes in JBR quality were correlated to the drying temperature and drying media used. SHS drying at 150 °C decelerated TBA formation the most. The proposed mathematical model and associated equations can predict changes in TBA during storage accurately and be applied to JBR under most drying conditions.
Keywords: Drying; Jasmine brown rice; Modelling; Rancidity